2023
DOI: 10.1123/ijspp.2022-0493
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Complex Relationship Between Internal and External Training Load: A Data-Driven Approach

Abstract: Background: Training load is typically described in terms of internal and external load. Investigating the coupling of internal and external training load is relevant to many sports. Here, continuous kernel-density estimation (KDE) may be a valuable tool to capture and visualize this coupling. Aim: Using training load data in speed skating, we evaluated how well bivariate KDE plots describe the coupling of internal and external load and differentiate between specific training sessions, compared to training imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Firstly, despite the recommendation to assess both internal and external training load parameters for insights into training stress ( Halson, 2014 ), there is currently no standardized direct coupling of internal and external training loads ( van der Zwaard et al, 2023 ). Using weightlifting athlete training data as an example, this study quantifies athletes’ external load and analyzes their training duration.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, despite the recommendation to assess both internal and external training load parameters for insights into training stress ( Halson, 2014 ), there is currently no standardized direct coupling of internal and external training loads ( van der Zwaard et al, 2023 ). Using weightlifting athlete training data as an example, this study quantifies athletes’ external load and analyzes their training duration.…”
Section: Discussionmentioning
confidence: 99%
“…One studies have proposed the use of plotting heart rate and velocity sequences (2-dimensional kernel density estimation-KDE) to couple internal and external loads, and found that ‘all training session types differed when comparing KDEs for heart rate and velocity’ (both p < 0.001; Van der Zwaard et al, 2023 ). The speed skating athletes investigated in this study applied various types of variable intensity training such as Extensive endurance, Extensive interval, Intensive endurance, Tempo, Sprint, etc.…”
Section: Discussionmentioning
confidence: 99%